Nature, Purpose, and Norm: A Program in American Philosophy. Issue 4 (24th January 2017) - STOVALL, PRESTON
ABSTRACT: For over a century there has been a protracted effort in American philosophy to use Darwinian explanatory resources in order to make certain leading ideas in German idealism naturalistically intelligible. I trace some of the nineteenth and twentieth century contours of this effort. In doing so I outline an understanding of ourselves as norm-laden persons in a natural world. As a consequence, philosophical inquiry—understood in C. S. Peirce's sense as the practice of the 'normative sciences' of aesthetics, logic, and ethics—can be understood as the self-conscious and rational exercise of natural and socially conditioned capacities to sense, think, and act. This leaves us with a project, by no means completed, to frame categories through which to understand the sociohistorical development of the notions of beauty, truth, and goodness as a process continuous with the natural evolution of the nervous system in its sensory, central, and motor moments.